AMPLITUDE SELF-ACTION OF HIGH-POWER CONTINUOUS RADIO WAVES IN THE IONOSPHERE: NUMERICAL SIMULATIONS - Chernogor, L. F.; Milovanov, Y. B. (Видавничий дім «Академперіодика», 2015)
Numerical simulations of the self-action of high-power continuous radio waves in the ionosphere caused by disturbances in electron temperature and density havebeen made for various frequencies, powers, and polarizations. It has been demonstrated that a major contribution to the self-action is made by the ionospheric D region where huge disturbances in electron temperature occur. In the E and F regions, the nocturnal electron temperature is also significantly disturbed, butthe self-action is relatively weak. The contribution to the selfaction from the disturbance in electron density at all altitudes is significantly smaller than that from the disturbance in electron temperature.Key words: ionosphere, high-power radio emission, numerical simulations, amplitude self-actioManuscript submitted 28.01.2015Radio phys. radio astron. 2015, 20(2): 122-132REFERENCES1.  GUREVICH, A. V. and SHVARTSBURG, A. B., 1973. Nonlinear Theory of Radio Wave Propagation in the Ionosphere. Moskow, Russia: Nauka Publ. (in Russian). 2.  GUREVICH, A. V., 1978. Nonlinear Phenomena in the Ionosphere. New York, Heildelberg, Berlin: Springer–Verlag. DOI:https://doi.org/10.1007/978-3-642-87649-3 3. CHERNOGOR, L. F.,  2014. Physics of High-Power Radio Emissions in Geospace : Monograph. Kharkiv, Ukraine: Kharkiv V. N. Karazin National University Publ. 4.  CHERNOGOR, L. F. and MILOVANOV, Y. B., 2015. Disturbances in the Ionosphere Produced by High-Power Continuous Radio Transmissions: Numerical Simulatins. Radio Phys. Radio Astron. vol. 20, no. 1, pp. 48–63 (in Russian). 5. BRYUNELLY, B. E. and NAMGALADZE, A. A.,  1987. Physics of the Ionosphere. Moskow, Russia: Nauka Publ. (in Russian). 6. GUREVICH, A. V. And SHLYUGER, I. S.,  1975. Investigations of nonlinear phenomena with a powerful radio pulse in the lower ionosphere. Izv. Vyssh. Uchebn. Zaved. Radiofiz. vol. 43, no. 9, pp. 1237–1260 (in Russian).